RANDOMNESS IDENTIFICATION VIA XOR REPOSITION IN LFSR A5/1'S SECOND BLOCK - Pallangan, Jorghie Theodore; Wowor, Alz Danny (Transpublika Publisher, 2024)
This study designs a random number generation method using the LFSR approach with the A5/1 scheme on three feedback functions. XOR is used as an operation in determining the value of the new bit output against the next iteration of the feedback function. Runs Test, Mono Bit, and Block bit, are used as test materials in producing random output against an input. The use of three feedback functions is used in testing, compared to previous studies that produce random numbers. In the plaintext and ciphertext encryption tests, it shows a